The Aesthetics of In/Authenticity: Buddhism, Commodification, and Ethnoreligious Belonging in a Sino-Tibetan Contact Zone - Brox, Trine (Numen, 2021)
Abstract This article investigates how the cultural politics of ethnoreligious belonging play out through everyday aesthetic practices at a market for Tibetan Buddhist objects in Chengdu, China – a multiethnic place that is perceived and experienced as “Tibetan” by the Tibetans and Chinese who work, live, and shop there. Based upon ethnographic research in Chengdu, I explore how Tibetan urbanites navigate the sensorially intense market, sorting its sights, sounds, and smells to determine who and what belongs as authentically Tibetan Buddhist. In the process, I argue, they are laying claim to an ability to feel the in/authentic acquired through being born and raised as a Tibetan. This practical ability is what I call an aesthetic habitus. Yet, many Tibetans fear this ability is being eroded; it is no longer clear who and what belongs, contributing to anxieties that Tibetans as a distinct ethnoreligious community will be extinguished.